Measuring the price of labour in agricultural economies: the shadow wage rate - Sharma, Bishnu Prasad (Economic Journal of Development Issues, 2015)
Labour market imperfections are one of the leading causes of economic backwardness that result in under utilization of labour, the most important input in production process. Labour markets are shallow in subsistence agricultural economies which causes problem in determining the wage rate. The household production function provides an alternative to estimating the shadow wage rate such that it reflects the opportunity cost of labour. The most important deductions of the household production function are: the marginal productivity of labour is its shadow wage rate and; at equilibrium, the marginal returns from labour are exactly equal across all activities. This paper uses data collected in 2008 in course of a leasehold forestry study from 297 households from Makwanpur district of Nepal using a multi stage sampling. This paper estimates the marginal productivity of labour in maize production, the most common form of economic activity, for male and female labour. It examines how the money wage rate and the actual wage rate may differ from the shadow wage rate reflected by marginal productivity of labour in agriculture. The findings reveal that the actual wage rate for male labour is inflated and exceeds its marginal productivity while female wage rate slightly understates its marginal productivity. The paper concludes with policy recommendation of ensuring institutional mechanisms to correct for these imperfections. DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11860 Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 24-35